A case study analysis : Telekom Malaysia BHD / Aziana Othman, Nor Fariza Mohd Faizal and Norsuhaida Mohd Bahari - Othman, Aziana; Mohd Faizal, Nor Fariza; Mohd Bahari, Norsuhaida (Faculty of Business and Management, 2001)
Syarikat Telekom Malaysia Berhad is the first company in Malaysia that involved in telecommunication industry. It also the first company that was incorporated by government on 12.10.1984. Telekom Malaysia has take over the operations of Jabatan Telekom Malaysia as part of the governments privatization exercise. Telekom Malaysia Berhad is one company that has many divisions in their organization. That is why they have rearranged their organization to implement SBU structure organization. The reason is they want to be more proactive and efficient in management.